Sosialisasi Pendidikan Karakter kepada Anggota Organisasi Pemuda Katolik Republik Indonesia (PMKRI) Cabang Jayapura Di Kota Jayapura - Aplonia D. Yonggom; Hendry Ch. Iwong; Golden Ringgo S.C. Ayomi; Mamberuman M. Inggamer; Sara Marlina Ohee (Universitas Cenderawasih, 2023)
implementation of this program is part of implementing the Tri Dharma Activities of higher education, namely community service. This activity was carried out together with community groups, namely the PMKRI youth organization or the Catholic Student Association of the Republic of Indonesia, Jayapura Branch, Papua Province. This is implemented through socialization to increase knowledge and understanding of character education. The aim of this activity is to increase knowledge and understanding of character education among participants who are members of the PMKRI organization, Jayapura Branch, Papua Province. The socialization activities were carried out one day using presentation, discussion and Focus Group Discussion methods as well as evaluation before and after the activity. By measuring the achievement of objectives from socialization activities. The number of participants involved was 16 people from the target of 20 participants. The results of the implementation of the socialization program went well and all participants were able to understand the definition and implementation of character education as well as the shared responsibility, especially the young generation of Papua, to participate in maintaining local wisdom values which are closely related to character education.